The role of catechol-O-methyltransferase in reward processing and addiction. - Tunbridge, E; Huber, A; Farrell, S; Stumpenhorst, K; Harrison, P; Walton, M (2012)
Catechol-O-methyltransferase (COMT) catabolises dopamine and is important for regulating dopamine levels in the prefrontal cortex. Consistent with its regulation of prefrontal cortex dopamine, COMT modulates working memory and executive function; however, its significance for other cognitive domains, and in other brain regions, remains relatively unexplored. One such example is reward processing, for which dopamine is a critical mediator, and in which the striatum and corticostriatal circuitry are implicated. Here, we discuss emerging data which links COMT to reward processing, review what is known of the underlying neural substrates, and consider whether COMT is a good therapeutic target for treating addiction. Although a limited number of studies have investigated COMT and reward processing, common findings are beginning to emerge. COMT appears to modulate cortical and striatal activation during both reward anticipation and delivery, and to impact on reward-related learning and its underlying neural circuitry. COMT has been studied as a candidate gene for numerous reward-related phenotypes and there is some preliminary evidence linking it with certain aspects of addiction. However, additional studies are required before these associations can be considered robust. It is premature to consider COMT a good therapeutic target for addiction, but this hypothesis should be revisited as further information emerges. In particular, it will be critical to reveal the precise neurobiological mechanisms underlying links between COMT and reward processing, and the extent to which these relate to the putative associations with addiction.